Economic, Demographic, and Institutional Determinants of Life Insurance Consumption across countries - Beck, Thorsten; Webb, Ian (Washington, DC: World Bank, 2014)
Life insurance has become an increasingly important part of the financial sector over the past 40 years, providing a range of financial services for consumers and becoming a major source of investment in the capital market. But what drives the large variation in life insurance consumption across countries remains unclear. Using a panel with data aggregated at different frequencies for 68 economies in 1961-2000, this article finds that economic indicators such as inflation, income per capita, and banking sector development and religious and institutional indicators are the most robust predictors of the use of life insurance. Education, life expectancy, the young dependency ratio, and the size of the social security system appear to have no robust association with life insurance consumption. The results highlight the importance of price stability and banking sector development in fully realizing the savings and investment functions of life insurance in an economy.